Índices econômicos sob a perspectiva de análises antecedentes, inovação e mercado de trabalho - Freitas, Andreia Pereira de (2020)
This research seeks to understand the dynamics of production, bringing in the first essay the theme of confidence indexes (which capture, through expectations, people's behavior under a given economic scenario), in the second essay, innovation, as a means of economic growth and in the third essay, the focus is the labor market, as one of the elements that makes production happen. The first article aims to analyze consumer sentiment surveys (consumer confidence surveys) and business surveys (investor surveys); investigating and understanding, reporting and describing how these indexes are seen in the literature, and how they interfere with production. It concludes that the Consumer Sentiment Index (ISC) and Investor Sentiment Index (ISI) are important in forecasting and / or anticipating the trend of economic cycles; identifying six different perceptions for the ISC and two large groups of perceptions for the ISI: one that links ISI to economic fluctuation; and another that relates ISI to the stock market (especially profitability). The second essay, understands that innovation is the result of a set of dimensions (Scientific and Technological Performance, Education, Infrastructure, Economic Environment, Investments and Public Policies), makes use of the Factor Analysis methodology and the World Bank database in period from 2010 to 2017, for the creation of the Innovation Capacity Index (ICI). ICI made it possible to know the nation's innovation potential, making it possible to monitor it over time; in addition to contributing to the orientation of investment decision-making and public policies. The third essay presents the labor market as the center of analysis, aiming at the creation of a synthesis index of the labor market, which contemplates the whole complex that the theme involves and which indicates the situation it is in. The research uses the Principal Component Analysis (ACP) method of Factor Analysis and uses data from the PNAD Continuous, National Household Sample Survey, from the first quarter of 2012 to the fourth quarter of 2018. The essay concludes that the Labor Market Synthesis Index (ISMT) was able to communicate through a grade the state of the labor market, allowing it to be monitored over time; besides allowing a look by state, respecting its particularities.